FEATURES OF SPATIAL DIFFERENTIATION OF SNOW COVER IN LOW-MOUNTAIN LANDSCAPES OF THE RUSSIAN ALTAI (CASE STUDY OF THE MAIMA RIVER BASIN) - L. F. Lubenets; D. V. Chernykh; D. K. Pershin (Лëд и снег, 2018)
The paper presents results of snow route measurements carried out during two winter seasons (2014/15 and 2015/16) over the period of maximum snow accumulation. The region of investigation was mainly the lowmountain basin of the river Maima (North, North-East Altai). Meteorological conditions for these periods (amounts of precipitation and mean monthly temperatures) were compared with climatic data (1985– 2016). The results obtained allowed establishing a relationship between the spatial and temporal variability of the snow depth, density and SWE (snow-water equivalent) and the weather conditions, orographic features (exposure and steepness of slopes), and characteristics of the underlying surface. The winter of 2014/15 was warm and moderately snowy season, while the winter of 2015/16 was warm but with small amount of snow. At the subtype level of the landscapes the maximum values of the snow cover thickness and the snow storage were observed in the chern-taiga landscapes, and the smallest ones – in the sub-taiga part of the basin area. The maximum snow storages (SWE) are characteristic for the secondary small-leaved forests and meadows, where these values exceed similar ones under the indigenous fir trees by 30%.